PEMBERDAYAAN MASYARAKAT ASEMROWO MELALUI PELATIHAN PEMBUATAN KONEKTOR MASKER GUNA MENINGKATKAN EKONOMI KREATIF - Muhammad Nabiel Azra; Dhea Nanda Safira; Indira Kusumawardhani; Desti Agustia Putri; Irma Yuhesti; Dani Fajariyatusyarifah; Ikrima Noka Wardani; Fiiryal Regina Hidayah; Indhi Regitha Pramesti; Melyana Sihotang; Gideon Setyobudiwitjaksono (Nusantara Hasana Berdikari, 2022)
This community service journal provides ideas on how to empower the community in Asemrowo Village through mask connector training, with the goal of providing knowledge and expertise so that residents who participate in the training can improve the welfare of Asemrowo Village residents following the current pandemic. A group of 32 KKNT-MBKM UPN